Biochar has positive but distinct impacts on root, shoot, and fruit production in beans, tomatoes, and willows - Sheffield, Sunniva B.; Hoefer, Taylor A.; Petersen, John E. (Frontiers in Sustainable Food Systems, 2024)
Positive relationships have been documented between the amount of biochar added to soils and various aspects of plant growth and fertility such as root, shoot, and fruit production. However, these effects depend on biochar source materials, soil characteristics and species of plant examined. This makes it impossible to systematically compare and generalize findings across previous studies that have used different soils and biochar. We conducted a novel investigation to assess the effects of a single source of biochar (hazelnut wood), in a constructed organic soil, on the different plant tissues in three functionally distinct species: tomatoes (Solanum lycopersicon), green beans (Phaseolus vulgaris), and willow (Salix sp.). Five levels of biochar soil amendment were assessed: 0% (control), 3%, 9%, and 26% by dry weight. We found a highly significant positive relationship between biochar concentration and total plant biomass (roots + shoots + fruits) in all species, with no significant difference in total biomass response among species. Fruit production increased with increased biochar in both beans and tomatoes. However, tomatoes exhibited significant differences in response among plant tissues; fruit production and shoot biomass increased significantly with biochar, but root tissue did not. Bean germination success increased significantly with biochar concentration. Date of first flowering was earlier with increasing soil biochar in beans but not in tomatoes. Control over both sources of biochar and soil composition in this experiment enables us to conclude that biochar addition can have different impacts on different plants and, in some cases, species-specific impacts on different plant tissues and other measures of fertility. Our results are contrary to prior research that found inhibiting effects of biochar at levels comparable to our 26% treatment. Biochar impacts on soil properties such as CEC and percent base cation saturation do not explain our findings, leading us to conclude that microbial interaction with biochar is an important factor that may explain the positive impacts of soil biochar on plant fertility observed. Further research that repeats this experiment in other soil types, with other biochar sources, and with other plant species is necessary to determine the generalizability of these important findings.